SIMPLE THEORETICAL FORMULA TO ADJUST AMOUNT OF REINFORCEMENT - Youkhanna, Kanaan Sliwo (European Scientific Journal, ESJ, 2015)
In construction industry, it is common practice that sometimes neither steel reinforcement may be available at market as required by design calculations nor poured concrete may be as strong as required. Such cases necessitate the modification of design calculations. A simple formula is required (for structural engineer as well as for site engineer) to adjust, quickly, the amount of reinforcement and to check that the adjusted materials (properties) will serve as the original ones as required in design calculations. Providing fy different than required by calculations is more safe because the adjusted calculations are done before pouring concrete. Providing fc’ larger than required by calculations is acceptable because it produces good concrete quality and enhances bending capacity. Providing fc’ less than required by calculations is not acceptable because it produces concrete of less quality than required. This may lead to failure. And may need some schemes to remedy. It is preferable to deal with fy being different than dealing with fc’ being different than required by calculations. Because the first case occur before pouring concrete and the second case occur after pouring concrete. A formula to adjust the calculations is set to predict the required provided steel ratio if fy is different than required by calculations.